Contrastive analysis of form and meaning of reduplication in Madurese and Minangkabau language - Santuso, Santuso; Sukarno, Sukarno (Journal of Language, Literature, Social and Cultural Studies, 2025)
Every language has its own uniqueness, sometimes making it challenging for speakers of one language to learn another. This research aims to describe the differences in form and meaning of reduplication between Madurese and Minangkabau languages. It is a qualitative descriptive study. The research data consists of reduplicated words in Madurese and Minangkabau sourced from previous research books. Data collection is conducted through observation method. The data analysis employs intralingual matching method. The results of this research indicate differences in reduplication systems between Madurese and Minangkabau: (a) reduplication in Madurese involves partial repetition, while in Minangkabau, it involves complete repetition; (b) there are 4 classes of words that can undergo reduplication in Madurese, compared to 6 words in Minangkabau; (c) reduplication with affixation in Minangkabau is more complex compared to Madurese; and (d) reduplication in Madurese yields 12 variations in meaning, whereas in Minangkabau, there are 8 variations.